Prediction of preterm delivery in symptomatic women using PAMG‐1, fetal fibronectin and phIGFBP‐1 tests: systematic review and meta‐analysis. (4th September 2018) - Melchor, J. C.; Khalil, A.; Wing, D.; Schleussner, E.; Surbek, D.
ABSTRACT: Objective: To assess the accuracy of placental alpha microglobulin‐1 (PAMG‐1), fetal fibronectin (fFN) and phosphorylated insulin‐like growth factor‐binding protein‐1 (phIGFBP‐1) tests in predicting spontaneous preterm birth (sPTB) within 7 days of testing in women with symptoms of preterm labor, through a systematic review and meta‐analysis of the literature. The test performance of each biomarker was also assessed according to pretest probability of sPTB ≤ 7 days. Methods: The Cochrane, MEDLINE, PubMed and ResearchGate bibliographic databases were searched from inception until October 2017. Cohort studies that reported on the predictive accuracy of PAMG‐1, fFN and phIGFBP‐1 for the prediction of sPTB within 7 days of testing in women with symptoms of preterm labor were included. Summary receiver–operating characteristics (ROC) curves and sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and positive (LR+) and negative (LR–) likelihood ratios were generated using indirect methods for the calculation of pooled effect sizes with a bivariate linear mixed model for the logit of sensitivity and specificity, with each diagnostic test as a covariate, as described by the Cochrane Handbook for Systematic Reviews of Diagnostic Test Accuracy. Results: Bivariate mixed model pooled sensitivity of PAMG‐1, fFN and phIGFBP‐1 for the prediction of sPTB ≤ 7 days was 76% (95% CI, 57–89%), 58% (95% CI, 47–68%) and 93% (95% CI, 88–96%), respectively; pooled specificity was 97% (95% CI, 95–98%), 84% (95% CI, 81–87%) and 76% (95% CI, 70–80%) respectively; pooled PPV was 76.3% (95% CI, 69–84%) ( P  < 0.05), 34.1% (95% CI, 29–39%) and 35.2% (95% CI, 31–40%), respectively; pooled NPV was 96.6% (95% CI, 94–99%), 93.3% (95% CI, 92–95%) and 98.7% (95% CI, 98–99%), respectively; pooled LR+ was 22.51 (95% CI, 15.09–33.60) ( P  < 0.05), 3.63 (95% CI, 2.93–4.50) and 3.80 (95% CI, 3.11–4.66), respectively; and pooled LR– was 0.24 (95% CI, 0.12–0.48) ( P  < 0.05), 0.50 (95% CI, 0.39–0.64) and 0.09 (95% CI, 0.05–0.16), respectively. The areas under the ROC curves for PAMG‐1, fFN and phIGFBP‐1 for sPTB ≤ 7 days were 0.961, 0.874 and 0.801, respectively. Conclusions: In the prediction of sPTB within 7 days of testing in women with signs and symptoms of preterm labor, the PPV of PAMG‐1 was significantly higher than that of phIGFBP‐1 or fFN. Other diagnostic accuracy measures did not differ between the three biomarker tests. As prevalence affects the predictive performance of a diagnostic test, use of a highly specific assay for a lower‐prevalence syndrome such as sPTB may optimize management. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from theabstract to view the translations.